Collaborative knowledge management systems for learning organisations - Abdullah, Rusli; Sahibudin, Shamsul; Alias, Rose Alinda; Selamat, Mohd Hasan (World Scientific Publishing, 2005)
A knowledge management system (KMS) is a concept that can be used for creating knowledge repositories, improving knowledge access and sharing as well as communicating through collaboration, enhancing the knowledge environment and managing knowledge as an asset for an institution or organisation. In this paper, we propose a collaborative KMS framework for learning organisations (LOs) and discuss components in the framework that will help organisations to increase productivity and quality as well as to gain return on investment from a KMS. These components are KMS functionality, architecture, taxonomy, psychological, sociocultural and audit.